2009
DOI: 10.1016/j.jbiosc.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of cuttlefish (Sepia officinalis) and sardine (Sardina pilchardus) viscera using commercial proteases: Effects on lipid distribution and amino acid composition

Abstract: Total lipid and phospholipid recovery as well as amino acid quality and composition from cuttlefish (Sepia officinalis) and sardine (Sardina pilchardus) were compared. Enzymatic hydrolyses were performed using the three proteases Protamex, Alcalase, and Flavourzyme by the pH-stat method (24 h, pH 8, 50 degrees C). Three fractions were generated: an insoluble sludge, a soluble aqueous phase, and an oily phase. For each fraction, lipids, phospholipids, and proteins were quantified. Quantitative and qualitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
2
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 45 publications
10
59
2
12
Order By: Relevance
“…Other authors, such as Lee (1995) and Sykes et al (2009) have already reported that concentrations of lipid in cephalopods are typically lower than 5% dw. The higher concentrations of lipid found for the other species of molluscs (A. brasiliana and I. bicolor) are in accordance with the use of whole bodies in the chemical analyses, since more lipid tend to be found in other tissues than in muscles (Kechaou et al, 2009;Monroig et al, 2013).…”
Section: Lipidsupporting
confidence: 76%
See 1 more Smart Citation
“…Other authors, such as Lee (1995) and Sykes et al (2009) have already reported that concentrations of lipid in cephalopods are typically lower than 5% dw. The higher concentrations of lipid found for the other species of molluscs (A. brasiliana and I. bicolor) are in accordance with the use of whole bodies in the chemical analyses, since more lipid tend to be found in other tissues than in muscles (Kechaou et al, 2009;Monroig et al, 2013).…”
Section: Lipidsupporting
confidence: 76%
“…According to Ogawa & Maia (1999), in muscles of fish humidity is around 80%. Depending on the species/taxonomic group, in marine invertebrates the humidity varies between 65% and 85% (e.g., Mol et al, 2008;Kechaou et al, 2009;Sykes et al, 2009;Zlatanos et al, 2009;Karthikeyan et al, 2011), with some exceptions such as jellyfish, which can reach levels of 95% humidity (Larson, 1986).…”
Section: Gross Chemical Profile General Pointsmentioning
confidence: 99%
“…In fact, a large quantity of water content is found in both male and female fresh MHG-HT (82.52 ± 0.56 %; 79.23 ± 0.39 %) and MHG-BB (79.28 ± 0.43; 80.04 ± 0.26%) respectively. These results correlate with those found in viscera cuttlefish captured in the Gulf of Gabes (south Tunisia) which are composed from 80% of water (79% in the viscera with ink and 75% for the viscera without ink) [15]. Ink of fresh sepia officinalis contains less water 65.54% only [16].This ink is composed mainly of water and other volatiles and organic substances and mineral substances [17].…”
Section: Discussionsupporting
confidence: 79%
“…Synowiecki and Al-khateeb (2000) observed similar values to our results for shrimp shell (29.2±0.2%). For CCV, ash values were more superior to the values found by Soufi-Kechaou et al (2009) for viscera of the same species collected from the same fishing area (2.0% w. w. b against 4.83%). The significant difference in amount of ashes was more important for CCV than CSH and the difference could be the result of heterogeneity in nutriments (shells, fishes and skeletons) remained in the stomach.…”
Section: Discussioncontrasting
confidence: 60%
“…Although, our value was superior to the moisture average values reported by Babu et al (2008) Abdelmouleh (1997) reported that moisture content varied from 75.9% (autumn) to 78.7% (spring) and the mean value (77.2%) was inferior to mean value found in our study. In addition, Castro, Garriw and Sow (1992) and Soufi-Kechaou et al (2009) obtained inferior values of moisture in S. officinalis viscera (74.4 and 77.2%). Difference in moisture amount may be explained by difference in anatomical structure of by-products as the shrimp head was supported by the shell, so water retention capacity could be different.…”
Section: Discussionmentioning
confidence: 94%